Estudo florístico e estrutural da família Orchidaceae em três inselbergues da Paraíba, Brasil - Almeida, Andréa (2016)
The composition and structure of the orchids populations in three inselbergs of the Paraíba State, Brazil, been analyzed. Floristics survey plants been collected fertile, between April of 2002 and July of 2003, whose samples been incorporated the Herbarium Jayme Coelho de Moraes (EAN), Centro de Ciências Agrárias/UFPB, and for phytossociology survey the parcels fixed method was used (ten parcels of 10x10 m), randoming distributed in inselbergs. Registered seven genus and nine species. Cyrtopodium polyphyllum (Vell.) ex Pabst. F. Barros it presented the number biggest of individuals (923), followed of Prescottia phleoides Lindl. (564) and Epidendrum cinnabarinum Jacq. (449), while the too much species less than 350 individuals each. Cyrtopodium polyphyllum, Epidendrum cinnabarinum and Prescottia phleoides had occurred in three studied environments, while Epidendrum secundum Jacq., Habenaria obtusa Lindl. and Pleurothallis ochreata Lindl., occurred in two and Brassovola tuberculata Hook., Cyrtopodium intermedium Brade and Encyclia longifolia Schlechter, only one. The species with better distribution was E. cinnabarinum, occurring 24 parcels (FRi = 21.43%). Registered five types of microhabitats, which type depressions in the rock presented higher diversity and the poor monocots mats. The high phytodiversity in the orchids flora occurred in inselbergs of Fagundes, followed of Esperança and Serraria and seems influenced to the outcrop size or situation of the inselbergs along a steep macroclimatical gradient. A comparison between orchids flora inselbergs of the South America confirmed that the outcrops Brazilian are presented distinct floristics, exactly when located geographically next. This fact also was evidenced for studied outcrops in the Pernambuco and Paraíba States, northeast region of Brazil.